Effect of ligand attachment on the C-I bond dissociation process on aluminum nanoclusters: a DFT investigation - Sengupta, Turbasu; Samanta, Bipasa; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The influence of the ligand attachment on the activation process of carbon halogen bond on small sized aluminum nanoclusters are investigated using density functional theory. Attaching suitable ligand to metal clusters is among the widely popular techniques often used by experimentalists in order to stabilize metastable clusters. In depth theoretical investigations have shown that based on the jellium configuration of the cluster, attaching an electron withdrawing ligand can either make a cluster more reactive toward the C-I dissociation or may convert the cluster relatively inert. The alteration of the activation barriers and other associated parameters due to ligand attachment are included in this paper along with additional calculations and explanations. The study also shows that even the reaction parameters of specific magic clusters can be significantly altered via ligand attachment. The activation process of small molecules on metal clusters are of crucial importance for the development of material science and cluster chemistry. The present investigation will therefore be useful for better understanding of the properties of the ligated clusters as well as may also aid the experimentalists toward controlling the reactivity of a specific cluster as required.